Are native Saccostrea glomerata and invasive Crassostrea gigas oysters' habitat equivalents for epibenthic communities in south-eastern Australia? - Wilkie, E M; Bishop, M J; O'Connor, W A (Journal of Experimental Marine Biology and Ecology, 2012)
Introduced species that alter the physical structure of marine habitats can have large impacts on biodiversity. We assessed whether in south-eastern Australia the invasive Pacific oyster, Crassostrea gigas, differs from the native Sydney rock oyster, Saccostrea glomerata, in the biogenic habitat that it provides to epibiotic communities. We also assessed how within a species (S. glomerata), genotype influences habitat provision. First, we conducted a field experiment in which we compared recruitment of epibiota to concrete plates with either C. gigas, wild-stock S. glomerata, selectively bred S. glomerata or glue (control). Second, we assessed whether within wild S. glomerata populations invaded by C. gigas, communities of epibenthos are correlated to the ratio of non-native to native oysters. On experimental plates C. gigas grew larger, and experienced higher mortality than both selectively-bred and wild-stock S. glomerata at each of two heights on the shore. The two genotypes of S. glomerata, by contrast, displayed similar rates of growth and mortality. The differing growth patterns among oyster types had not, however, translated to consistent differences in the composition of associated benthic communities by 12. months following establishment of experimental treatments. Within established wild oyster assemblages, C. gigas were typically much larger than on our experimental plates, and the non-native influenced the abundance of several epibiotic taxa, although not the identity of species present. Where impacts of C. gigas on the abundance of associated benthic species occurred, they were generally negative. Overall, our results indicate that while differences in the population size-structure of C. gigas and S. glomerata may be evident from small-scale experiments, the detection of flow-on effects to associated epibenthic communities may require approaches that incorporate much larger spatio-temporal scales. Nevertheless, the observation that wild C. gigas primarily influenced the abundance rather than the identity of associated epifauna suggests a certain degree of redundancy between the two species in their provision of habitat to epibiota. © 2012 Elsevier B.V.